THE ROLE OF CORRESPONDENTS OF THE ORENBURG DEPARTMENT OF THE RUSSIAN GEOGRAPHICAL SOCIETY IN THE STUDY OF THE CULTURE OF THE NOMADIC PEOPLES OF CENTRAL ASIA (Journal of history, 2025)
Since the firsthalf of the XVIIIcentury, theprocess of studyinggeography,ethnography,historyandculture of the nomads of CentralAsiain the RussianEmpire began. The organizationandconduct of expeditionarystudies of the territory of traditionalcivilizations of thisvastregioncontributed to the creation of geographicalmaps,scientificresearchon the history,linguistics,economicsandethnography of the nomads of CentralAsia.With the completion of the integration of KazakhstanintotheRussianEmpire, the scientificstudy of the region has firmly become partof the activities of centralgovernmentagenciesandvariousgroups of researchers.Russians Russian Geographical Society's scientific article is devoted to the study of the history of the Orenburg Department of the Russian Geographical Society. It presents an analysis of the programs and instructions of the ethnographic department, the formation and creation of a correspondent network of the Orenburg Department of the Russian Geographical Society for the study of the history and culture of the nomadic peoples of Central Asia in the second half of the 19th century.The purpose of the workis to analyze the creation of a correspondentnetworkas a result of the successfulimplementation of programs of the ethnographicdepartment of the society.After all, the range of interests of scientificsocieties was notlimitedonly to scientificresearch,activeeducationalwork was alsocarried out among the nomadicpopulation,which was most oftenrealizedthrough the involvement of localresidentsinconductingsurveys,conversationson the study of customs and traditions of the Turkic-speaking peoples,readingpopularsciencelecturesamong the nomads of Eurasia, the functioning of museumsandlibraries,participationinexhibitions,publicationarticles,reportsinjournals of scientificsocietiesandotherperiodicals.The research work was based on the data of documents from Russian archives and the scientific works of Kazakhstani and foreign scientists, the works of Russian historians. Analyzing historical research, the authors have done a lot of work aimed at carrying out a scientific study of the peculiarities and traditions, ethnography and culture of the outskirts of the Russian Empire at the turn of the XVIII-XIX centuries.
Keywords: scientific society, expeditions, ethnography, history, programs, reports, correspondent network